Leading with Humility in Technology-intensive work Environments: Building Engagement through Satisfaction in Indonesia’s Gaming Sector - Agustian Budi Prasetya; Fathimah Prajna Iswari (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The dynamic and technology-intensive gaming industry is frequently challenged by high work pressure, heavy mental workloads, and employee turnover risks that may undermine work engagement. This study examines the mediating role of job satisfaction in the relationship between leadership humility, psychological empowerment, and work engagement among 218 office-based employees in the Indonesian gaming industry. Using a quantitative approach, data were collected through a five-point Likert scale questionnaire and analyzed using PLS-SEM. The findings reveal that leadership humility (β = 0.235, t = 4.423, p < 0.001) and psychological empowerment (β = 0.559, t = 10.661, p < 0.001) significantly enhance job satisfaction, which in turn positively influences work engagement (β = 0.658, t = 10.671, p < 0.001). Interestingly, neither leadership humility (β = -0.080, p = 0.260) nor psychological empowerment (β = -0.005, p = 0.957) exerts a significant direct effect on work engagement, indicating a full mediating role of job satisfaction (indirect effects: β = 0.154 and β = 0.368, respectively; p < 0.001). Grounded in Self-Determination Theory (SDT) and Social Exchange Theory (SET), this study highlights the importance of human-centered leadership and humane organizational practices in addressing the intense pressures of technology-driven work environments.